Factors Affecting Nursing Students’ Attitude Towards Research: A Survey in a Philippine Higher Education Institution - Ryan Michael Flores Oducado (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2021)
Introduction: Research is one of the competencies expected of a beginning professional nurse. While research attitude has been widely explored among nursing students internationally, there is limited published research among nursing students in the Philippines. Objective: This study was conducted to find out the factors associated with attitude towards research among nursing students. Method: The design of this study cross-sectional with 79 undergraduate third-year nursing students in one higher education institution in the Philippines as participants. The Attitude Toward Research scale was the primary data collection tool. Differences in research attitude were tested using t-test and one-way ANOVA. Results: The results indicated that nursing students generally had positive attitude towards research. Graduates of public junior and senior high schools, those who had experience doing research in junior high school, and those who had presented in a research conference outside their school had significantly better research attitude. In addition, differences in research attitude were also noted based self-rated level of research knowledge, competence, and readiness. Conclusion: Type of high school, prior experience, knowledge, competence, and readiness in conducting research were significant factors influencing nursing students’ research attitude. Nursing schools should continue to raise and cultivate the positive attitude of students towards scientific investigation.